2004
DOI: 10.1002/asi.20103
|View full text |Cite
|
Sign up to set email alerts
|

A flexible interface design for Web directories to accommodate different cognitive styles

Abstract: Search engines are very popular tools for collecting information from distributed resources. They provide not only search facilities, but they also offer directories for users to browse content divided into groups. In this paper, we've adopted an individual differences approach to explore user's attitudes towards various interface features provided by existing Web directories. Among a variety of individual differences, cognitive style is a particularly important characteristic that influences the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…These findings concur with many studies suggesting that students' SEVs should play an essential role in how they process and organize scientific information (Songer & Linn, 1991;Tsai, 1998aTsai, , b, 2000. In addition to increasing attention for the development of the adaptive learning system concerned with the user's cognition status (Chen, Magoulas, & Dimakopoulos, 2005), the system designer should highlight the role of SEVs on increasingly metacognitive engagement with science information on the Web. Furthermore, it should be noted that there was one possible exception to the aforementioned conclusion, since in this study the agreement toward a particular SEV dimension, 'Social Negotiation in Science', was found to be related to both advanced and less sophisticated standards of judging online science information.…”
Section: Discussionmentioning
confidence: 99%
“…These findings concur with many studies suggesting that students' SEVs should play an essential role in how they process and organize scientific information (Songer & Linn, 1991;Tsai, 1998aTsai, , b, 2000. In addition to increasing attention for the development of the adaptive learning system concerned with the user's cognition status (Chen, Magoulas, & Dimakopoulos, 2005), the system designer should highlight the role of SEVs on increasingly metacognitive engagement with science information on the Web. Furthermore, it should be noted that there was one possible exception to the aforementioned conclusion, since in this study the agreement toward a particular SEV dimension, 'Social Negotiation in Science', was found to be related to both advanced and less sophisticated standards of judging online science information.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable volume of research has examined student learning style in webbased instructional contexts (Chen, Margoulas, & Dimakopoulos, 2005).…”
Section: Learning Style 619mentioning
confidence: 99%
“…This result meets the founds of Kennedy (2014), when the researcher found that the autonomy of the student is directly related to its capacity for analysis, synthesis and organization of their routine studies. According to Chen, Magoulas and Dimakopoulos (2005), we found that the habits of the distance students must be considered in the planning of these courses. Their styles and learning strategies should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Distance learning assumes some characteristics such as motivation to study, personal interest, commitment, autonomy, self-direction and management of own learning strategies. This requires an active role of student in relation to their knowledge construction and autonomy (Chen, Magoulas, & Dimakopoulos, 2005;Riding & Sadler-Smith, 1997). …”
Section: Introductionmentioning
confidence: 99%